The Reductionist Implications of Outcome-Based Education in Malaysian Architectural Education - FAKRI ZAKY JAAFAR, MOHAMAD (Enquiry The ARCC Journal for Architectural Research, 2025)
Architecture is a discipline that requires the integration of a wide spectrum of knowledge. This holistic nature of architecture is reflected in earlier architectural education. However, the recent trend in pedagogical development in education is characterized by the admiration of a positivist outlook that favour a reductionist approach in education, specifically the introduction of Outcome-Based Education (OBE). The need to maintain a higher education status by architectural education providers in Malaysia requires adherence to the standards stipulated by the public higher education authority and the Malaysian Quality Agency (MQA). This paper argues that there is a reductionist tendency in the standards, specifically in its stipulation on the use of OBE and its mapping process, a trend in the 1990s arising out of a positivist outlook. The reductionist undertone of this mechanism affects the quality of architectural education, resulting in undesirable outcomes. The most pressing concern is the effect of a reductionist mindset on creativity and a holistic view.